The New Avalanche-Like Stochastic Model for Parameterization of Seismicity and Its Application to the South Sakhalin Island Seismicity - M. V. Rodkin; I. N. Tikhonov (International Journal of Geophysics)
Seismic process is usually considered as an example of occurrence of the regime of self-organizing criticality (SOC). A model of seismic regime as an assemblage of randomly developing episodes of avalanche-like relaxation, occurring at a set of metastable subsystems, can be the alternative of such consideration. The model is defined by two parameters characterizing the scaling hierarchical structure of the geophysical medium and the degree of metastability of subsystems of this medium. In the assemblage, these two parameters define a model b-value. An advantage of such approach consists in a clear physical sense of parameters of the model. The application of the model for parameterization of the seismic regime of the south part of Sakhalin Island is considered. The models of space changeability of the scaling parameter and of temporal changeability of the parameter of metastability are constructed. The anomalous increase of the parameter of metastability was found in connection with the Gornozavodsk and Nevelsk earthquakes. At the present time, high values of this parameter occur in the area of the Poyasok Isthmus. This finding is examined in comparison with other indications of an increase in probability of occurrence of a strong earthquake in the South Sakhalin region.